Tutors’ Corrective Feedback and Students’ Preferences in an English Course at Kampung Inggris Pare, Indonesia - Maghfiroh, Shinta Amalia; Wahyuni, Sri; Edi Winarto, Agus (English Education:Journal of English Teaching and Research, 2024)
This study aimed to identify the kinds of corrective feedback that tutors and students most frequently utilize. The research design used in this study was qualitative, involving 2 English tutors and 25 students from an English course institution. To collect data, the researcher conducted observation to observe 6 class interaction meetings. Then, the researcher distributed Google form questionnaires to students via WhatsApp and interviewed two tutors. Data analysis began with summarizing and then displaying, reducing, and displaying. The last step was to interpret and represent the data. The results showed that English tutors in Kampung Inggris give recasts more often than other corrective feedback due to the students' tendency to receive corrective feedback. However, two corrective feedback were often used after recast: repetition and paralinguistic. Unfortunately, these two types of corrective feedback are not very favorable to students. In fact, almost half the number of participants disagree (40%) and (44%), respectively. This needs to be considered by teachers to minimize misunderstandings, maximize the learning process, and improve students' speaking skills without making students depressed and offended by getting corrective feedback.